2001
DOI: 10.1523/jneurosci.21-24-09896.2001
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of Pain by Anxiety Is Associated with Activity in a Hippocampal Network

Abstract: It is common clinical experience that anxiety about pain can exacerbate the pain sensation. Using event-related functional magnetic resonance imaging (FMRI), we compared activation responses to noxious thermal stimulation while perceived pain intensity was manipulated by changes in either physical intensity or induced anxiety. One visual signal, which reliably predicted noxious stimulation of moderate intensity, came to evoke low anxiety about the impending pain. Another visual signal was followed by the same,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
452
5
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 725 publications
(511 citation statements)
references
References 98 publications
34
452
5
7
Order By: Relevance
“…Clinical and preclinical studies have demonstrated that altered sensitivity to noxious stimuli, or increased incidence and severity of chronic pain, is associated with a large number of disorders of the central nervous system, including depression Dworkin et al, 1995;Klauenberg et al, 2008;Shi et al, 2010a;Shi et al, 2010b;Terhaar et al, 2010), anxiety disorders (Asmundson and Katz, 2009;Finn et al, 2006;Geuze et al, 2007;Ploghaus et al, 2001;Rivat et al, 2010), multiple sclerosis (Kenner et al, 2007;Olechowski et al, 2009;Solaro et al, 2003) and others. Thus, a passive-avoidance paradigm using air-puff in place of noxious foot-shock may also be preferable for assessment of aversive learning and memory in rodent models of these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and preclinical studies have demonstrated that altered sensitivity to noxious stimuli, or increased incidence and severity of chronic pain, is associated with a large number of disorders of the central nervous system, including depression Dworkin et al, 1995;Klauenberg et al, 2008;Shi et al, 2010a;Shi et al, 2010b;Terhaar et al, 2010), anxiety disorders (Asmundson and Katz, 2009;Finn et al, 2006;Geuze et al, 2007;Ploghaus et al, 2001;Rivat et al, 2010), multiple sclerosis (Kenner et al, 2007;Olechowski et al, 2009;Solaro et al, 2003) and others. Thus, a passive-avoidance paradigm using air-puff in place of noxious foot-shock may also be preferable for assessment of aversive learning and memory in rodent models of these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous studies of cortical areas involved with the pain response. For example, the entorhinal cortex of the hippocampal formation has been shown to respond differentially to identical noxious stimuli depending on whether the perceived pain intensity was enhanced by pain-relevant anxiety [25]. Additionally, Villemure and Bushnell [26] recently reported that painrelated activity within the anterior cingulate, medial thalamus and primary and secondary somatosensory cortices was correlated with mood, whereas the effects of attentional state altered activity in anterior insular cortex.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the anticipation of pain activates brain regions in close proximity to brain regions activated by pain itself (Ploghaus et al, 1999). In an interesting human study, subjects were given visual cues to an impending noxious stimulus (Ploghaus et al, 2001). One group of subjects was given a consistent moderate noxious stimulus following a visual cue while another group was given random and intermittent noxious stimuli mixed with the 13 moderate stimulus following a visual cue.…”
Section: The Importance Of the Type Of Noxious And Aversive Stimulimentioning
confidence: 99%